Self-Assembled InAs(N) Quantum Dots Grown by Molecular Beam Epitaxy on GaAs (100)* - Pulzara-Mora, Alvaro; Rojas-Ramírez, Juan Salvador; García, Victor Hugo Méndez; Huerta-Ruelas, Jorge A.; Alvarez, Julio Mendoza; López, Maximo López (IntechOpen, 2012)
None